2008
DOI: 10.1021/ja802341q
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Entropic Coiling and Poor Solvent Effects in Protein Collapse

Abstract: The early events in protein collapse and folding are guided by the protein's elasticity. The contributions of entropic coiling and poor solvent effects like hydrophobic forces to the elastic response of proteins are currently unknown. Using molecular simulations of stretched ubiquitin in comparison with models of proteins as entropic chains, we find a surprisingly high stiffness of the protein backbone, reflected by a persistence length of 1.2 nm, which is significantly reduced by hydrophobic forces acting bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 27 publications
1
53
0
Order By: Relevance
“…The lowest l p value further matches the typical pitch distance for a -helix while the second value adequately compares to the typical pitch distance for an -helix 36, 37 or -13 helix rise per amino acids. [38][39][40] This result is in good agreement with conformation of the fimbrial subunits that are characterized by -sheet for FimH (Ig-like domains) whereas the stacking of FimA leads to formation of -helix structure. Altogether, the above results indicate that the obtained persistence length that reflects the very flexibility of the FimH adhesin, is not affected with increasing pulling rates at fixed solution pH.…”
Section: The Retraction Force Curves Depicted In Figures 2a 2b Were supporting
confidence: 81%
“…The lowest l p value further matches the typical pitch distance for a -helix while the second value adequately compares to the typical pitch distance for an -helix 36, 37 or -13 helix rise per amino acids. [38][39][40] This result is in good agreement with conformation of the fimbrial subunits that are characterized by -sheet for FimH (Ig-like domains) whereas the stacking of FimA leads to formation of -helix structure. Altogether, the above results indicate that the obtained persistence length that reflects the very flexibility of the FimH adhesin, is not affected with increasing pulling rates at fixed solution pH.…”
Section: The Retraction Force Curves Depicted In Figures 2a 2b Were supporting
confidence: 81%
“…Investigations by several theoretical groups (40)(41)(42)(43) have suggested that a hydrophobic polymer in solution will collapse into a surface area-minimized globule (such as those seen by AFM scans; see Fig. 1A) and that forcing a part of the polymer into solution causes the polymer to assemble into coexisting chain and globule regions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This roughly corresponds to the length of a single amino acid. However, in more recent studies it has been suggested that this measured value of p accounts for both entropic and attractive interactions due to hydrophobic contacts within a protein [100].…”
Section: The Worm-like Chain Modelmentioning
confidence: 99%